A study on merchandise performance analysis in Pos 2020 Dayabumi / Nurizan Mohd. Zin - Mohd. Zin, Nurizan (Faculty of Business Management, 1999)
Merchandise performance is the most important determinant factor to the retailer. There are numerous models to measure merchandise performance, and one of them is ABC Analysis. The ABC Analysis will be able to measure which product is more preferred by the customers. POS 2020 Dayabumi is a franchising industry which is moving towards a better time. Merchandise performance considered by the management of POS 2020 Dayabumi as its main objective to increase their sales.